The meaning of the blood urea nitrogen/creatinine ratio in acute kidney injury - Uchino, Shigehiko (Clin Kidney J, 2012)
BACKGROUND. A blood urea nitrogen (BUN)/creatinine ratio (BCR) >20 (0.081 in international unit) is used to distinguish pre-renal azotemia (PRA) and acute tubular necrosis (ATN). However, there is little evidence that BCR can distinguish between these two conditions and/or is clinically useful. METHODS. We conducted a retrospective study using a large hospital database. Patients were divided into three groups: ‘low BCR’ (if BCR when acute kidney injury (AKI) developed was ≤20), ‘high BCR’ (if BCR when AKI developed was >20) and ‘no AKI’ if patients did not satisfy any of the Risk, Injury, Failure, Loss and End-stage kidney disease criteria for AKI during hospitalization. RESULTS. Among 20 126 study patients, 3641 (18.1%) had AKI. Among these patients, 1704 (46.8%) had a BCR <20 at AKI diagnosis (‘low BCR’) and 1937 (53.2%) had a BCR >20 (‘high BCR’). The average BCR for the two groups was 15.8 versus 26.1 (P < 0.001). Hospital mortality was significantly less in the ‘low-BCR’ group (18.4 versus 29.9%, P < 0.001). Multivariable logistic regression analysis for hospital mortality (‘no AKI’ as a reference) showed that the odds ratio of ‘high BCR’ (5.73) was higher than that of ‘low BCR’ (3.32). CONCLUSIONS. Approximately half of the patients with AKI have a BCR >20, the traditional threshold of diagnosing PRA. Unlike PRA patients who have a lower mortality than ATN patients, high BCR patients had higher hospital mortality compared with low BCR patients, which was confirmed with multivariable analysis. These findings do not support BCR as a marker of PRA.